The Influence of Human Resource Practices on the Retention of Core Employees - SHEHNAZ SAHIB ZADA; DR. SHAHID JAN; SYED IMRAN KHAN; MUHAMMAD ABDUL HASEEB (Journal of Business & Tourism, 2021)
The retention of core employees is one of the challenges many of business organizations facing today. For many organizations, strategic staffing has become a concern because the ability to hold on to highly talented core employees can be crucial to future survival. This empirical study examined the current human resource management (HRM) practices of Higher education institution of Khyber Pakhtunkhwa in the retention of their core employees. In particular, the research identified the core elements of HRM practices, which strongly influence the decision for core employees to stay. With the rapid growth and introduction of new public and private sector universities in Khyber Pakhtunkhwa, it became difficult to retain employees. The current study focuses on employees of both public and private sector universities in order to extract information about employee choice and critically examines HR practices and factors, which may influence employees to stay and work for organization. Analyzing the existing Human Resources Management literature, there are very few studies have been conducted regarding Human Resource Management practices on retention of core employees. This raises uncultivated issues such as: which factor of HRM, influences retention of core employees in higher education institution of Khyber Pakhtunkhwa. These unexplored and uncultivated issues will be the focal point of this study. Furthermore, this study will explore & press forward the HRM literature on the rising trends of the 21st century.